Exposition aux organophosphorés en milieu rural nigérien : étude de l’activité enzymatique érythrocytaire des cholinestérases comme indicateur biologique - Abdou Mamadou; Ali Doumma; Ahmed Mazih; Baba Moussa Coulibaly (VertigO)
The amount of the erythrocyte acetylcholinesterase is a good indicator of professional exposure to organophosphorus and carbamates pesticides. The study related to 103 agreeing people, including 91% of men with an age of 43 ± 16 years and a body weight of 65 ± 17 kg; and 9% of women with an age 38 ± 15 years and a body weight of 67 ± 21 kg. All these people are implied in pesticide application in year 2006 in 4 of the countries of Niger where the problem of the acridians arises with more acuity. The clinical examination and the anamnestic investigations carried out into the participants in this study, revealed neither of serious clinical antecedents, nor of case poisonings to the pesticides. The Test-Mate ChE, based on a photometric system, was used to measure the acetylcholinesterase activities in the erythrocytes after an exposure to these pesticides. The average cholinesterasemy of pre-exposure of the 103 people is of 3.63 ± 0.61 U/ml, with 3.57 ± 0.53 U/ml for the men and 3.48 ± 0.44 U/ml for the women, this difference is not significant. After the exposure to organophosphorus, a low reduction of the cholinesterasemy of the 103 people was observed compared to their pre-exposure (baseline) measurements of AChE, it was of 3.21 ± 0.17 U/ml; with 3.48 ± 0.44 U/ml for the women and 3.57 ± 0.53 U/ml for the men. Seventeen people (16.50%) of 103 showed a hypocholinesterasemy, because their inhibition rate varied from 31% to 36%. The reduction of the enzymatic activity in the bodies of some of the applicators (9 people) largely exceeded the biological threshold recommended by the World Health Organization which is 30%, but no cholinergic syndrome was detected.